Accretion history of the Trans-Hudson Orogen in Manitoba and Saskatchewan from paleomagnetism - Symons, David TA; Harris, Michael J (Canadian Journal of Earth Sciences, 2005)
Lithoprobe's sponsorship has led to the acquisition of paleomagnetic data from ~20 units throughout the Paleoproterozoic Trans-Hudson Orogen (THO) of Saskatchewan and Manitoba, essentially the first such data for the region. Discussed summarily in this paper, they provide an initial framework for the THO's tectonic evolution. They show that the Archean Hearne and Superior cratons were at subtropical and subpolar paleolatitudes, respectively, at ~1875 Ma, with the Lynn Lake LaRonge arc midway between them in the Manikewan Ocean. By ~1855 Ma, this ocean was still ~5500 ± 700 km wide, and its seafloor was subducting northwestward under the Hearne craton and pericratonic Peter Lake domain margin with the coeval development of an Andean-type continental magmatic arc, the WathamanChipewyan batholith. Between ~1855 and ~1810 Ma, coalescing apparent polar wander path (APWP) segments record closing of the ocean at a rate of ~12 cm/a, trapping and accreting the several separate intervening terranes (Flin Flon, Hanson Lake, Lynn Lake LaRonge, Rottenstone, and presumably also other THO terranes). From ~1815 to ~1775 Ma, the assembled terranes drifted as a coherent craton, yielding a stillstand and hairpin in the APWP.